Efficient Water‐Splitting Device Based on a Bismuth Vanadate Photoanode and Thin‐Film Silicon Solar Cells. Issue 10 (19th August 2014) - Han, Lihao; Abdi, Fatwa F.; van de Krol, Roel; Liu, Rui; Huang, Zhuangqun; Lewerenz, Hans‐Joachim; Dam, Bernard; Zeman, Miro; Smets, Arno H. M.
Abstract A hybrid photovoltaic/photoelectrochemical (PV/PEC) water‐splitting device with a benchmark solar‐to‐hydrogen conversion efficiency of 5.2 % under simulated air mass (AM) 1.5 illumination is reported. This cell consists of a gradient‐doped tungsten–bismuth vanadate (W:BiVO4) photoanode and a thin‐film silicon solar cell. The improvement with respect to an earlier cell that also used gradient‐doped W:BiVO4 has been achieved by simultaneously introducing a textured substrate to enhance light trapping in the BiVO4 photoanode and further optimization of the W gradient doping profile in the photoanode. Various PV cells have been studied in combination with this BiVO4 photoanode, such as an amorphous silicon (a‐Si:H) single junction, an a‐Si:H/a‐Si:H double junction, and an a‐Si:H/nanocrystalline silicon (nc‐Si:H) micromorph junction. The highest conversion efficiency, which is also the record efficiency for metal oxide based water‐splitting devices, is reached for a tandem system consisting of the optimized W:BiVO4 photoanode and the micromorph (a‐Si:H/nc‐Si:H) cell. This record efficiency is attributed to the increased performance of the BiVO4 photoanode, which is the limiting factor in this hybrid PEC/PV device, as well as better spectral matching between BiVO4 and the nc‐Si:H cell.